Answer:
2x + 3y - 4 = 0
Explanation:
Equation of the line → 2x - 3y + 4 = 0
3y = 2x + 4
y =
![(2)/(3)x+(4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/vw7w6bz3ysbenaxdpbnfiefhkozpt9adlf.png)
Slope of this line 'm' =
![(2)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9l76ru6jxv4fv4b8lpmxx1u47fxut8ydly.png)
y-intercept of this line → y =
Or
![(0, (4)/(3))](https://img.qammunity.org/2022/formulas/mathematics/high-school/nf1lowkxhamlcvaruoli18ui2s0yg7jqeg.png)
Let the equation of the line is,
y = m'x + b'
By the property of perpendicular lines,
m × m' = -1
![(2)/(3)* m'=-1](https://img.qammunity.org/2022/formulas/mathematics/high-school/qhsyl77j5qrlv8v7twrz8khvv9fl6itf00.png)
m' =
![-(3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rcukpxy0gnr3qb07cn9qccmybzy90s50px.png)
Equation of the perpendicular line will be,
y =
![-(3)/(2)x+b'](https://img.qammunity.org/2022/formulas/mathematics/high-school/jn1uisfsulnnd99wh2s2qwyyi52wz8be2k.png)
Since this line passes through
,
![(4)/(3)=-(3)/(2)* 0+b'](https://img.qammunity.org/2022/formulas/mathematics/high-school/a138gs2gs7dabr9vsendicocscdv98ctpz.png)
b' =
![(4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/ml6ineffmlt4emj78bb6pjch86mxt3po9o.png)
Therefore, equation of the perpendicular line will be,
y =
![-(2)/(3)x+(4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/b1zhwlnpc4j9bbbquq9jhxywzvx1czgrrl.png)
3y = -2x + 4
2x + 3y - 4 = 0